Workshop Pembuatan Media Pembelajaran Berbasis Android untuk Pendidik Mata Pelajaran Geografi di Kota Jayapura - Sahrul Akbar; Muh. Riswan; Putri Ellen Gracia Risamasu; Suci Elisabeth Samallo (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
This community service aims to improve the knowledge and skills of Geography subject educators in Jayapura City in creating Android-based learning media. The activity was carried out through a workshop involving 16 educators and focused on the use of the Smart Apps Creator application as a tool for developing interactive learning media. The method used is the classical method which includes the stages of preparation, design, development, and simulation. The workshop was held at the community service partner school, namely SMA Muhammadiyah, Jayapura City. The results of the activity showed that participants experienced a significant increase in knowledge and skills, as evidenced by the results of the pretest and posttest with an average increase of 2.31 points. All participants succeeded in producing an Android-based learning media application that can be used directly in classroom learning. In addition to having a positive impact on improving the digital competence of educators, this activity also opens up opportunities for ongoing collaboration between universities and the teacher community. The conclusion of this activity is that a workshop that is designed practically and applicatively is able to provide a real contribution to the development of learning quality through the use of relevant and easily implemented digital technology in schools.